2022
DOI: 10.1158/1078-0432.ccr-22-0588
|View full text |Cite
|
Sign up to set email alerts
|

Lenalidomide plus R-GDP (R2-GDP) in Relapsed/Refractory Diffuse Large B-Cell Lymphoma: Final Results of the R2-GDP-GOTEL Trial and Immune Biomarker Subanalysis

Abstract: Purpose: New therapeutic options are needed in relapsed/refractory diffuse large B-cell lymphoma (R/R DLBCL). Lenalidomide-based schedules can reverse rituximab refractoriness in lymphoma. Experimental Design: In the phase II R2-GDP trial, 78 patients unsuitable for autologous stem cell transplant received treatment with the following schedule: lenalidomide 10 mg Days (D)1–14, rituximab 375 mg/m2 D1, cisplatin 60 mg/m2 D1, ge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Greater advances has been observed in the treatment of patients with DLBCL, however, primary refractory and relapse remain as a common problem, actually, only 48 to 59% of patients remain alive free disease at 10 years [14,15]. Multiple schedules has been proven, basically including anthracycline based chemotherapy with doses dense, or adding to CHOP or R-CHOP, some of the new drugs, as ibrutinib, lenalidomide, bortezomib, but some Improvement in Response Rate (ORR), DFS and OS did nor show any statistical improved in outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Greater advances has been observed in the treatment of patients with DLBCL, however, primary refractory and relapse remain as a common problem, actually, only 48 to 59% of patients remain alive free disease at 10 years [14,15]. Multiple schedules has been proven, basically including anthracycline based chemotherapy with doses dense, or adding to CHOP or R-CHOP, some of the new drugs, as ibrutinib, lenalidomide, bortezomib, but some Improvement in Response Rate (ORR), DFS and OS did nor show any statistical improved in outcome.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, the major problem is relapse, various attempts, has been employed, neither has been observed that the use of interferon, interferon and chemotherapy and rituximab, employed as maintenance or consolidative has been benefit to these patients [2][3][4][5]. Recently, et, reported that the used of lenalidomide employed during induction and followed by 18 months of lenalidomide as maintenance therapy, and an statistical difference in those patients, they employed low doses of lenalidomide, and not delayed or reduced the doses, probably in this instance not is necessary high doses, and continued low doses will be better [15]. In our institution lenalidomide is not available, or these reason we employed thalidomide at low doses, also for 18 months.…”
Section: Discussionmentioning
confidence: 99%
“…47 Several other studies have suggested that lenalidomide can safely be used with chemotherapy and other anti-cancer agents (Table 2). [48][49][50] Several next-generation compounds, with increased affinity for cereblon and specificity for Ikaros and Aiolos, termed CELMoDs, are in development including avadomide, iberdomide, and golcadomide.…”
Section: Lenalidomide and Novel Celmodsmentioning
confidence: 99%
“…Several other studies have suggested that lenalidomide can safely be used with chemotherapy and other anti‐cancer agents (Table 2). 48–50 …”
Section: Investigational/novel Therapiesmentioning
confidence: 99%
“…The combination of lenalidomide plus rituximab (R 2 ) exhibited enhanced anti-tumor activity in several B-cell NHL patients regardless of front-line or R/R settings, especially in indolent lymphomas [250][251][252][253][254][255]. Lenalidomide, combined with R-CHOP as front-line therapy, showed promising ORRs and PFS in both FL and DLBCL [256,257]. The mTOR inhibitor and the immunomodulatory agent have overlapping effects within the PI3K/AKT/ mTOR axis with synergistic potential.…”
Section: Combinations With Imidsmentioning
confidence: 99%